Mediamorphosis: Assessing the influence of digital media on traditional newspapers in Nigeria from the audience and media managers’ perspectives - Patrick Ene Okon; Presly Ruke Obukoadata; Lawrence Ekwok (World of Media, 2022)
There is an ongoing debate that conventional print media are becoming seriously threatened and facing possible extinction due to the penetrating presence of the digital media. This paper discusses, from the perspectives of the audience and media managers, the situation as it evolves in Nigeria. Applied and survey research methods are adopted for the study. Roger Fidler’s theory of Mediamorphosis and the Toronto School’s Medium theory constitute the theoretical framework. The study identifies that traditional print media are becoming endangered due to low circulation figure, dwindling advertisement revenue, and even closures of newspaper businesses. It, therefore, concludes that change has indeed swept through the media environment, and conventional media in Nigeria should adapt to this change in order to remain relevant. In recommending the way forward, the paper advises Nigerian newspaper owners and managers to create new ideas, new value propositions, and new ways to engage with customers so as to improve on their revenue and ultimately remain in business.